Evaluation of trained volunteer doula services for disadvantaged women in five areas in England: women's experiences - Darwin, Zoe; Green, Josephine; McLeish, Jenny; Willmot, Helen; Spiby, Helen (Wiley, 2016)
Disadvantaged childbearing women experience barriers to accessing health and social care services and face greater risk of adverse medical, social and emotional outcomes. Support from doulas (trained lay women) has been identified as a way to improve outcomes; however, in the UK doula support is usually paid-for privately by the individual, limiting access among disadvantaged groups. As part of an independent multi-site evaluation of a volunteer doula service, this study examined women's experiences of one-to-one support from a trained volunteer doula during pregnancy, labour and the post-natal period among women living in five low-income communities in England. A mixed methods multi-site evaluation was conducted with women (total n = 137) who received the service before December 2012, using a combination of questionnaires (n = 136), and individual or group interviews (n = 12). Topics explored with women included the timing and nature of support, its impact, the relationship with the doula and negative experiences. Most women valued volunteer support, describing positive impacts for emotional health and well-being, and their relationships with their partners. Such impacts did not depend upon the volunteer's presence during labour and birth. Indeed, only half (75/137; 54.7%) had a doula attend their birth. Many experienced volunteer support as a friendship, distinct from the relationships offered by healthcare professionals and family. This led to potential feelings of loss in these often isolated women when the relationship ended. Volunteer doula support that supplements routine maternity services is potentially beneficial for disadvantaged women in the UK even when it does not involve birth support. However, the distress experienced by some women at the conclusion of their relationship with their volunteer doula may compromise the service's impact. Greater consideration is needed for managing the ending of a one-to-one relationship with a volunteer, particularly given the likelihood of it coinciding with a period of heightened emotional vulnerability.